TOXICITY OF SEA GRASS EXTRACT (Eucheuma cottonii AND Gracillaria sp) TO LARVA Artemia salina - Putra, Danil Rama; Mulyadi, Aras; Zulkifli, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Seaweed is a source of foreign exchange, namely as the main export product and a source of income for coastal communities. Previous research on species Eucheuma cottonii and Gracillaria sp contain bioactive compounds that can be used in medicine, for example as anti-cancer. The purpose of this study was to determine the LC50 value and safe concentration of Artemia salina larvae. The research was conducted at the Chemical Oceanography Laboratory of the Department of Marine Sciences, Faculty of Fisheries and Marine, Riau University in July 2020. The method used in this research is the experimental method. The results of the research on the toxicity of the n-hexane extract of seaweed E. cottonii and Gracillaria sp had bioactivity compounds against A. salina shrimp larvae, indicated by a small LC50 value (<1000 ppm), namely 62.62 ppm for E. cottonii and 83.55. ppm for Gracillaria sp, so it is included in the toxic category. According to research by experts, if the extract or compound tested is less than 1000 ppm, it is considered that there is biological activity. For a safe concentration for the survival of A. salina, 6.262 ppm for E. cottonii and 8.355 ppm for Gracillaria sp.